The Importance of Balanced Nutrition for Children's Health in Cilengkrang State Elementary School - Dini Afriani; Gita Arisara; Dini Justian; Ariyanti; Nurlinda Tri Wahyuningsih; Rahma Putri Indriani; Siti Yulia Rahmawati; Yusuf Rohdiansyah (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Balanced nutrition is an important concern in supporting the growth and development of children in Indonesia. Cilengkrang State Elementary School located in North Sumedang District is one of the focuses in efforts to increase knowledge about the importance of balanced nutrition. The implementation of this community service aims to increase students' knowledge about balanced nutrition and increase students' knowledge about nutritious food as an effort to prevent disease in school-age children. This community service activity was carried out in October 2024. The focus of this community service activity is to increase students' knowledge about balanced nutrition and efforts to prevent disease in school-age children through the introduction of nutritious food. Students take a pre-test before presenting the counseling with the aim of finding out their knowledge about balanced nutrition and nutritious food. The counseling is carried out offline, including counseling on balanced nutrition, nutritious food, the benefits of nutritious food and the impact of not consuming enough nutritious food. The students re-took a post-test after being given counseling with the aim of finding out their knowledge after being given counseling. The results after being given counseling, the students' knowledge about balanced nutrition and nutritious food increased. This activity went smoothly and the students were very enthusiastic about listening to the counseling.